Simulating the Dynamics of Quantum Dots Using Hierarchy of Pure States - Toivonen, Sebastian (My University, 2023)
Quantum dots are tiny semiconductor systems, typically a few nanometers in size, possessing unique properties due to their size and structure. Over the last few decades, quantum dots have received significant attention and have several potential applications. For instance, they can be utilized as single-photon sources and few-emitter laser sources, and potentially as physical qubits in quantum computing, leveraging their capability to confine and control individual electrons. Typically, quantum dots are formed by growing them on semiconductor surfaces. As a result of this growth method, quantum dots confine electrons in space, effectively rendering them as zero-dimensional, causing their energy levels to become quantized. Consequently, quantum dots can be conceived of as artificial atoms, and many phenomena typical to atoms, such as resonance fluorescence and emission of single photons, can be experimentally observed. Theoretically, a single quantum dot represents a fundamental open quantum system and therefore offers an avenue for studying fundamental processes of open quantum systems, such as decoherence and thermalisation. Numerous approaches and techniques have been developed to study the dynamics of open quantum systems. In this thesis, we focus on the non-Markovian quantum state diffusion (NMQSD) formalism, especially the hierarchy of pure states (HOPS) method. NMQSD can be used to solve the dynamics of open quantum systems that are linearly coupled to non-Markovian environments. In some special cases, the solution can be obtained exactly, but in general, approximations are needed. HOPS is a numerically exact method developed to solve the NMQSD equation without the use of approximations. In this thesis, we study a quantum dot placed in a cavity that is coupled to environmental vibrations. Using HOPS, we simulate the dynamics of the quantum dot, including processes like absorption and resonance fluorescence, and compute response functions. The aim is to demonstrate the applicability of the HOPS method in solving the dynamics of quantum dots, even in problematic parameter regimes.

Kvanttipisteet ovat pieniä, muutamien nanometrien kokoisia puolijohdesysteemejä, joilla on ainutlaatuisia ominaisuuksia niiden koon ja rakenteen ansiosta. Kvanttipisteet ovat saaneet paljon huomiota viimeisten vuosikymmenien aikana, ja niillä on useita mahdollisia sovelluskohteita. Esimerkiksi niitä voidaan käyttää yksifotonilähteinä ja laserlähteinä, sekä mahdollisesti fyysisinä kubitteina kvanttilaskennassa, hyödyntäen niiden kykyä kontrolloida yksittäisiä elektroneja. Tyypillisesti kvanttipisteitä muodostetaan kasvattamalla niitä puolijohteiden pinnoilla. Tämän kasvatustavan seurauksena kvanttipisteet vangitsevat elektroneja paikka-avaruudessa, joka tekee niistä efektiivisesti nollaulotteisia, jolloin niiden energiatasot ovat kvantittuneet. Näin ollen kvanttipisteitä voidaan ajatella keinotekoisina atomeina, ja monet atomeille tyypilliset ilmiöt, kuten resonanssifluoresenssi ja yksittäisten fotonien emissio, ovat kokeellisesti havaittavissa. Teoreettisesti kvanttipiste edustaa perustavanlaatuista avointa kvanttisysteemiä. Tämän vuoksi kvanttipisteiden tutkiminen tarjoaa mahdollisuuden tutkia avointen kvanttisysteemien keskeisiä ilmiöitä ja prosesseja, kuten dekoherenssia ja termalisaatiota. Avointen kvanttisysteemien dynamiikan tarkasteluun on kehitetty useita lähestymistapoja ja menetelmiä. Tässä työssä syvennytään ei-Markoviseen kvanttitiladiffuusioformalismiin (engl. non-Markovian quantum state diffusion, NMQSD) ja erityisesti puhtaiden tilojen hierarkiamenetelmään (engl. hierarchy of pure states, HOPS). NMQSD-formalismin avulla voidaan ratkaista avointen kvanttisysteemien dynamiikkaa, kun ne ovat kytkeytyneet ei-Markoviseen ympäristöön. NMQSD-yhtälön ratkaiseminen onnistuu joissain erikoistapauksissa tarkasti, mutta usein vaaditaan approksimaatioiden käyttöä. HOPS on numeerisesti tarkka menetelmä, joka on kehitetty ratkaisemaan NMQSD-yhtälö ilman approksimaatioita. Tässä tutkielmassa tarkastellaan kvanttipistettä kaviteetissa, joka on kytköksissä ympäristön hilavärähtelyihin. Käyttäen HOPS-menetelmää simuloidaan kvanttipisteen ominaisuuksia, kuten absorptiota ja resonanssifluoresenssia, sekä lasketaan vastefunktioita. Tavoitteena on osoittaa HOPS-menetelmän tehokkuus kvanttipisteiden dynamiikan tutkimisessa myös vaikeissa parametrialueissa.
Keywords: quantum dot, cavity, hierarchy of pure states, HOPS, absorption spectrum, emission spectrum, response function, non-Markovian dynamics